2015
DOI: 10.1017/s1742170515000423
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of cover crop mixtures and bio-waste composts enhance biomass production and nutrients accumulation: a greenhouse study

Abstract: Improved farming practices are needed to produce more food in a sustainable way. This study assessed 12 combinations of cover crop mixtures and amendment treatments and their effects on shoot and root dry (matter (DM) weights, nitrogen (N), phosphorus (P) and potassium (K) uptakes in plants, Mehlich-3 extractable P (PM3) and K (KM3). Shoot and root DM weights were increased by 30–63% with combinations of clover-based cover crop mixtures and 65 Mg ha−1 of municipal solid food waste (MSFW) compared with syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It is difficult, therefore, to draw general conclusions about cover crop mixtures due to the inherent differences in systems depending on the specific components. Mixtures frequently outperform single species in terms of biomass production and P uptake (Li et al 2007(Li et al , 2014Messiga et al 2016), in addition to the positive influence plant biodiversity exerts on soil biology. Other plants growing in close association with P-mobilizing plants confer additional benefits through intercropping or undersowing, and may also increase access to sparingly-soluble P (Li et al 2007).…”
Section: Cover Crop Mixturesmentioning
confidence: 99%
“…It is difficult, therefore, to draw general conclusions about cover crop mixtures due to the inherent differences in systems depending on the specific components. Mixtures frequently outperform single species in terms of biomass production and P uptake (Li et al 2007(Li et al , 2014Messiga et al 2016), in addition to the positive influence plant biodiversity exerts on soil biology. Other plants growing in close association with P-mobilizing plants confer additional benefits through intercropping or undersowing, and may also increase access to sparingly-soluble P (Li et al 2007).…”
Section: Cover Crop Mixturesmentioning
confidence: 99%
“…An important role of legacy soil P in supporting crop P requirements has been reported in a Spodosol in Florida (Obour et al, 2011; Silveira et al, 2013), and in Cambisols and Luvisols in Germany (Ohm et al, 2017). Similar to P removal by crop harvest, net drawdown of soil P reserves in grazing lands occurs by harvest of livestock products, and the eventual impoverishment of grazing lands by P removal may be a growing problem worldwide (Messiga et al, 2015; Sattari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The P balances we report here are consistent with previous studies. For perennial grasses, Obour et al (2011) reported a negative P balance (−10.8 kg P ha −1 year −1 ) in unfertilized bahiagrass managed for hay production in Florida; and Messiga et al (2015) reported negative (ranging from −4.5 to −2.0 kg P ha −1 year −1 ) and positive P balances (ranging from 2.0 to 26.0 kg P ha −1 year −1 ) in grassland sites receiving lower and higher P fertilization, respectively, across Switzerland and Canada. For corn, P surpluses have been reported in continuous corn and corn‐wheat systems fertilized with P (Zhang et al, 2020), while other studies reported P deficits in conventional corn in spite of P fertilization (Maltais‐Landry et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant size actually reflected the amount of the nutrient demands and the size of the nutrient sink, given that the total nutrient accumulation and nutrient demand by reproductive organs increased with increasing plant biomass (Fig. and Appendix S4; see also Zhu et al., ; Marschner, ; Sardans and Peñuelas, ; Messiga et al., ). Thus, a plant with a large body potentially has large nutrient sink pools with high nutrient flux through the plant body.…”
Section: Discussionmentioning
confidence: 99%